High Incidence of Veno-Occlusive Disease With Myeloablative Chemotherapy Following Craniospinal Irradiation in Children With Newly Diagnosed High-Risk CNS Embryonal Tumors: A Report From the Children's Oncology Group (CCG-99702) - Nazemi, Kellie J.; Shen, Violet; Finlay, Jonathan L.; Boyett, James; Kocak, Mehmet; Lafond, Deborah; Gardner, Sharon L.; Packer, Roger J.; Nicholson, H. Stacy (Pediatric blood & cancer, 2016)
Background The outcomes with high‐risk central nervous system (CNS) embryonal tumors remain relatively poor despite aggressive treatment. The purposes of this study using postirradiation myeloablative chemotherapy with autologous hematopoietic stem cell rescue (ASCR) were to document feasibility and describe toxicities of the regimen, establish the appropriate dose of thiotepa, and estimate the overall survival (OS) and event‐free survival (EFS). Procedure The Children's Cancer Group conducted this pilot study in children and adolescents with CNS embryonal tumors. The treatment consisted of induction chemotherapy to mobilize hematopoietic stem cells, chemoradiotherapy, and myeloablative consolidation chemotherapy with ASCR. Results The study accrued 25 subjects in 40 months and was closed early due to toxicity, namely, veno‐occlusive disease (VOD) of the liver, more recently termed sinusoidal obstructive syndrome (SOS). Of 24 eligible subjects, three of 11 (27%) receiving thiotepa Dose Level 1 (150 mg/m2/day × 3 days) and three of 12 (25%) receiving de‐escalated Dose Level 0 (100 mg/m2/day × 3 days) experienced VOD/SOS. One additional subject experienced toxic death attributed to septic shock; postmortem examination revealed clinically undiagnosed VOD/SOS. The 2‐year EFS and OS were 54 ± 10% and 71 ± 9%, respectively. The 5‐year EFS and OS were 46 ± 11% and 50 ± 11%. Conclusions The treatment regimen was deemed to have an unacceptable rate of VOD/SOS. There was complete recovery in all six cases. The overall therapeutic strategy using a regimen less likely to cause VOD/SOS may merit further evaluation for the highest risk patients.